Social Networking Sites Use and Relationship Satisfaction among Married Adults: The Mediating Effect of Materialism - Bukhari, Rubab; Bashir, Rabia; Perveen, Shagufta (Annals of Human and Social Sciences, 2024)
The main objective of the current study was to examine the association between materialism, social networking sites use, and relationship satisfaction among married adults. While extensive research exists on social networking sites use and relationship satisfaction, materialism's mediating role among married adults in Pakistan is unclear and this study addresses this gap. Through convenient sampling, 390 married adults were approached in a cross-sectional study from various districts of AJK and KPK. The researchers utilized the Material Value Scale (MVS), Modified Facebook Intrusion Questionnaire (MFIQ), and Relationship Assessment Scale (RAS) to evaluate the variables. Results showed significant positive correlation between materialism, social networking sites use, and relationship satisfaction. Mediation analysis confirmed that materialism partially mediates the relationship between social networking sites use and relationship satisfaction.